Cut Slope Stability Analysis on Terrain with Slope at Besishahar, Lamjung - Poudyal, Aabha; Dahal, Apoorwa; Shrestha, Jasmine; Timilsina, Manita (International Journal on Engineering Technology, 2024)
Building construction on sloped terrain presents a myriad of challenges that necessitate specialized engineering solutions and careful planning. Though the cut slopes are prone to failure, the increase in urbanization makes construction in such landscape inevitable. The complex topography of this region poses significant scientific and technological challenges, demanding innovative solutions for slope stability analysis and effective mitigation measures. This study incorporates geotechnical and geological study of the Manab Sewa Ashram Site in Besishahar, the cut slope failure analysis using Limit Equilibrium Method and Kinematic failure analysis and suggesting mitigating measure. Three different profiles with critical slopes were selected to represent the overall area for Slope Stability modeling and Kinematic Failure Analysis. The calculation of Factor of Safety for slope stability was done using Slide v.6.020 software under Rocscience package. Since non-engineered cutting of slopes is predominantly existing in the context of Nepal, slope management contributes by majorly focusing on the safety of the structure on or around the slopes.